The possible critical role of T-cell help in DSA-mediated graft loss - Süsal, Caner; Slavcev, Antonij; Pham, Lien; Zeier, Martin; Morath, Christian (Transplant international, 2018)
In this review, we discuss a possible central role of T-cell help in severe forms of graft damage mediated by donor-specific HLA antibodies (DSA). Some kidney transplant recipients with pretransplant DSA show a high graft failure rate, whereas in other patients DSA do not harm the transplanted kidney and in most cases, disappear shortly after transplantation. Analyzing 80 desensitized highly immunized kidney transplant recipients and another multicenter cohort of 385 patients with pretransplant HLA antibodies, we reported recently that an ongoing T-cell help from an activated immune system, as measured by an increased level of soluble CD30 in serum, might be necessary for the DSA to exert a deleterious effect. Patients positive for both pretransplant DSA and sCD30 appear to require special measures, such as the elimination of DSA from the circulation, potent immunosuppression, good HLA-matching, and intense post-transplant monitoring, whereas exclusion of DSA-positive patients from transplantation in the absence of high sCD30 may not be justified in all cases, even if the pretransplant DSA are strong and complement-activating.
Keywords: antigen Ki-1; protilátky; kohortové studie; Graft Survival; Isoantibodies; Immunosuppressive Agents; Cohort Studies; isoprotilátky; Tissue Donors; Graft Rejection; HLA antigeny; dárci tkání; T-lymfocyty; komplement; Renal Insufficiency; renální insuficience; Antibodies; Animals; Complement System Proteins; lidé; Ki-1 Antigen; Kidney Transplantation; transplantace ledvin; Humans; zvířata; rejekce štěpu; přežívání štěpu; HLA Antigens; myši; T-Lymphocytes; Mice; imunosupresiva